Resource management in the next-generation DS-CDMA cellular networks. - Jihui Zhang (IEEE Wireless communications)
Direct sequence code-division multiple access has been shown as the predominant access technology to provide high-speed multimedia services in next-generation wireless cellular networks. The DS-CDMA cellular network significantly differentiates itself from the traditional narrowband TDMA/FDMA system, in which great capacity gain can be explored by taking advantage of its unique characteristics. This article addresses resource management in DS-CDMA cellular networks. We first provide an overview of the DS-CDMA network and discuss the main challenges in the design of resource management schemes. We then examine several critical issues within the scope of resource management, including congestion control, rate and power control, and cell planning, with the emphasis on call admission control. Finally, we offer some insights and discussions on the performance aspects, strengths, and weaknesses of existing proposals.